Pemberdayaan Masyarakat Desa Melalui Pelatihan Teknis Operasional Mesin Cetak Pelet bagi Kelompok Budidaya Ikan Kelurahan Beji Kabupaten Semarang - Sri Tutie Rahayu; Dewa Gede Alit Astawa; Arif Rakhman Suharso; Wahyu Ari Putranto; Sandy Setyawan (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This service aims to increase the knowledge and skills of the fish farming group in Beji Village, Semarang Regency, regarding the operational technicalities of pellet printing machines to empower village communities. The method used in this service was training, which included lectures, questions and answers, and direct practice in making fish food pellets with material provided to participants, including knowledge of tool operation, tool components, and troubleshooting on tools. This service partner was a fish farming group in Beji Village, East Ungaran District, to improve the community's economic level around the new campus of the Indonesian State Maritime Polytechnic in Ngobo sub-district, which borders Beji sub-district. This service evaluation instrument used an assessment of the training participants by practicing operating, disassembling, and installing spare parts for the fish pellet printing machine themselves. The results of this service showed that most members of the fish farming group in Beji sub-district could operate the fish pellet press and care for it well. Apart from that, the quality and quantity of catfish feed increased because the the fish farming group had been able to produce fish feed independently.